2021
DOI: 10.1016/s1556-0864(21)02046-3
|View full text |Cite
|
Sign up to set email alerts
|

204P Immune-related adverse events (IrAEs) as a predictor of response to immunotherapy in patients with lung cancer

Abstract: Results: 76 patients were included. Patient characteristics and toxicities are summarized in the table. 55.3% patients presented toxicity: 30.9%, 45.2% and 23.8% grade I, II and III respectively (attending CTCAE v5.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have reported a positive association between the incidence of irAEs and the survival outcomes ( 6 , 61 , 62 ), while others have found no such association ( 63 ). A systematic review and meta-analysis has shown that grade ≥3 toxicities were correlated with a better overall response rate, but poor overall survival ( 64 ), while another has linked irAEs with better survival and response ( 7 ).…”
Section: Toxicity Itself As a Biomarkermentioning
confidence: 99%
“…Several studies have reported a positive association between the incidence of irAEs and the survival outcomes ( 6 , 61 , 62 ), while others have found no such association ( 63 ). A systematic review and meta-analysis has shown that grade ≥3 toxicities were correlated with a better overall response rate, but poor overall survival ( 64 ), while another has linked irAEs with better survival and response ( 7 ).…”
Section: Toxicity Itself As a Biomarkermentioning
confidence: 99%